Benefits and challenges of Documentary Video for Social Learning: A Systematic Review - Pratama, Andhika Yudha; Yafie, Evania; Wijaya, Daya Negri; Masruroh, Heni (Universitas Negeri Malang, 2025)
Social learning refers to the process of observation through which individuals acquire and refine behaviors. It plays a crucial role in helping individuals differentiate between appropriate and inappropriate actions. Documentary videos can enhance this learning process by providing observational opportunities through the figures depicted in the videos. This article reviews studies on the advantages and challenges of using documentary videos in social learning. A systematic literature review method was employed, incorporating 23 studies—18 focusing on the benefits and 5 addressing the challenges of documentary videos. The studies were collected from Google Scholar, Taylor & Francis, Elsevier, Wiley, and SAGE Journals. The findings indicate that documentary videos contribute to performance improvement and behavioral development. However, a major challenge lies in the lack of standardized guidelines for documentary video production. Future research should explore strategies to address these challenges and optimize the effectiveness of documentary videos in social learning.